Carbon Sequestration in the Trees of Community Forest:: A Case Study of Hasantar Community Forest, Kathmandu, Nepal - Gautam, Ratna Silwal (International Journal of Applied Sciences and Biotechnology, 2019)
Carbon sequestration is one of the main ecosystem services in today’s condition. Estimation of above ground tree biomass and carbon stock is important as it gives ecological and economic benefits to the local people. This study was conducted in the Hasantar Community Forest (HCF) of Nagarjun Municipality, Kathmandu. Concentric circular plots of 12.62m radius were established in five different blocks of HCF for the study of tree species. The main objective of this study was to find out the Important Value Index (IVI), Above Ground Tree Biomass (AGTB) and carbon stocks tree species of HCF. This forest comprises the tree species of families like fagacaeae, moraceae, myrtaceae, fabaceae etc in dominant numbers. Schima wallichii was found ecologically most significant tree species as it possess highest IVI value. The carbon stock of this plant was found as 206.865 t/ha which comprises 27 % of total carbon in HCF. The total above ground tree carbon stock of HCF (55.4 ha.) was found 144.795 t/ha. Int. J. Appl. Sci. Biotechnol. Vol 7(1): 124-129